SWOT Analysis in Determining Rega Bakery and Cake Business Strategy in Langsa City - Junaida, Erni; Amilia, Suri; Hanum, Nurlaila; Ardianti, Dyah Ayu (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study is to determine the right and competitive business strategy in maintaining and developing the Rega Bakery and Cake bakery business in Langsa City. This type of research is qualitative research. Data collection was carried out by interviews and document studies. Source determination using purposive sampling technique. Data validity was tested by source triangulation. The data analysis method used is an analysis of the company's internal and external environment which is the basis for conducting a SWOT analysis. The results of the study are that Rega Bakery and Cake is in quadrant II and the strategy that must be implemented is a diversification strategy through market penetration by expanding market share through marketing/promotion efforts, market development by expanding market share geographically is a new area and product development by modifying the product . It is recommended that this business always improve service quality with the concept of Customer Oriented. Provide good facilities for customers. Carry out marketing activities on a regular basis with accuracy and precision and neatness to increase revenue.